PENGARUH INTELLECTUAL CAPITAL DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA) - Rulfah M. Daud; Abrar Amri (Jurnal Telaah dan Riset Akuntansi, 2008)
The purpose of this research is to examine the influence intellectual capital and corporate social responsibility disclosure to firm performance both simultaneously and partialy at manufacturing companies in Indonesia stock exchange. Data used is anually report and financial report.     This research use the hypotesis testing research with census method where the population are investigated. Total of population is 19 companies during two years (2006-2007). Observation, 50 total of population is 38 companies which analysed by multiple linear regression model.     The research result show that simultaneously, intellectual capital and CSR disclosure influence to firm performance. It explains that independent variabel coeficient (ether intellectual capital or CSR disclosure) is equall 0 (ß1 = -0,801 nad ß2 = 0,154). So that simultaneaously, intellectual capital and CSR disclosure influence to firm performance and partialy, intellectual capital to firm performance have negative influence. It denided the hypotesis which hope to firm performance have positive influence. Keyword : Intellectual capital, corporate social responsibility, firms performance